Can Analytical Mindset Save HR from Voodoo Practices?. Issue 2 (April 2019) - Ramesh, S.
Abstract: Be it employee recognition or goal setting, human resources function is based on proven research. However, of late it has been overrun by fads and best practices. Voodoo HR is looking at companies from a totally different milieu and copying practices that worked for them. 'Great place to work' and 'leadership development' are but two of the trends that have swept organisations. Every organisation is unique in terms of culture, values and the business challenges they face. A 'catch all' approach based on industry practices may not be a panacea for all such challenges. To be meaningful, human resources should return to their own evidences and analytics to solve the unique problems of their companies. It is not an easy path and it may be the 'in' thing to go with the fad of the moment, but ultimately solving the unique challenges gives HR a leverage that fads don't.